PELAKSANAAN PENGADAAN TANAH BAGI PEMBANGUNAN JALAN TOL UNTUK KEPENTINGAN UMUM(Studi Analisis Pembangunan Tol Cengkareng - Batu Ceper - Kunciran) - Jeremi Nico, (2021)
Land acquisition for public purposes often creates problems, given the limited availability of land and the population who already occupy the land is very dense. This study aims to analyze the implementation of land acquisition for toll road construction, by taking the case of the Cengkareng - Batu Ceper - Kunciran Toll Road. The method used in this research is normative juridical, prescriptive specification, with qualitative descriptive analysis. The results of this research show that toll road procurement is in accordance with the elements stipulated in Law no. 2/2012 which requires deliberation, public interest and compensation, in which the form of compensation in this case is in the form of money.